2001
DOI: 10.1016/s1097-2765(01)00360-4
|View full text |Cite
|
Sign up to set email alerts
|

Linkage of M-CSF Signaling to Mitf, TFE3, and the Osteoclast Defect in Mitfmi/mi Mice

Abstract: Osteoclasts are multinucleated hematopoietic cells essential for bone resorption. Macrophage colony-stimulating factor (M-CSF) is critical for osteoclast development and function, although its nuclear targets in osteoclasts are largely unknown. Mitf and TFE3 are two closely related helix-loop-helix (HLH) transcription factors previously implicated in osteoclast development and function. We demonstrate that cultured Mitf(mi/mi) osteoclasts are immature, mononuclear, express low levels of TRAP, and fail to matur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
101
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(104 citation statements)
references
References 52 publications
3
101
0
Order By: Relevance
“…Of note, certain nonmelanocyte lineages, such as osteoclasts, are severely abnormal in mice harboring homozygous dominant-negative MITF mutations, but much less affected by null mutations. This effect is likely because of the ability of dominant-negative MITF mutants that titrate out other MiT family members, such as TFE3 in osteoclasts (Weilbaecher et al, 1998(Weilbaecher et al, , 2001Steingrı´msson et al, 2002).…”
Section: Mitf As a Key Transcription Factor In The Pigment Biosynthesmentioning
confidence: 99%
“…Of note, certain nonmelanocyte lineages, such as osteoclasts, are severely abnormal in mice harboring homozygous dominant-negative MITF mutations, but much less affected by null mutations. This effect is likely because of the ability of dominant-negative MITF mutants that titrate out other MiT family members, such as TFE3 in osteoclasts (Weilbaecher et al, 1998(Weilbaecher et al, , 2001Steingrı´msson et al, 2002).…”
Section: Mitf As a Key Transcription Factor In The Pigment Biosynthesmentioning
confidence: 99%
“…It has also been shown that TFE3 binds the co-activator p300 in vivo (49). It was suggested that the precise E-box⅐TFE3, SBE⅐Smad, and TFE3⅐Smad interaction arrangements on the PAI-1 promoter allow for efficient recruitment of either CBP or p300 coactivator leading to enhanced transcription (26).…”
Section: Bcn-1 Element-dependent Activation Of the Laminin ␥1 Chain Genementioning
confidence: 99%
“…The heterodimer translocates to the nucleus where it binds one of the 5Ј SBE elements of the LAMC1 promoter that is appropriately bent by TFE3 and other DNA-bending factors. The interaction of TFE3 with the Smad heterodimer that follows generates a constructive topology for an effective recruitment of co-activators, such as CBP (33,49), and basal transcriptional machinery leading to enhanced LAMC1 gene transcription.…”
Section: Bcn-1 Element-dependent Activation Of the Laminin ␥1 Chain Genementioning
confidence: 99%
“…Mice homozygous null for TFE3 or TFEC had no recognized abnormalities (8), but TFEB nulls exhibited embryonic lethality associated with placental vascular defects (12). In addition, Mitf and TFE3 have been found to undergo identical modifications after cytokine stimulation (13), and MITF has been shown to directly regulate BCL2, a key apoptotic regulator, in a manner important for melanocyte and melanoma survival (14).…”
mentioning
confidence: 99%